Dating young zircon: A case study from Southeast Asian megacrysts. (1st April 2020) - Kirkland, Christopher L.; Danišík, Martin; Marsden, Ruby; Piilonen, Paula; Barham, Milo; Sutherland, Lin
Abstract: U-Pb geochronology of Quaternary zircon crystals is challenging due to their low levels of radiogenic-Pb, the importance of accurate common-Pb correction, and the potential need for secular disequilibrium correction. (U-Th)/He dating offers an independent benchmark for the quality of U-Pb data and their reduction, including the various corrections, as the closure temperature of the He system in zircon is <500 °C, whereas for Pb it is >900 °C. Hence, U-Pb ages must predate (U-Th)/He ages, or at least be equal to them in the case of rapid cooling. Analyses of southeast Asian mantle-derived zircon megacrysts from Tram Poung (TR), Tok Phrom (TO), Bang Kacha (BA), and Pailin (PA) provide new information about their pre-eruptive and eruptive history. SIMS U-Pb zircon ages of 6.7 ± 3.4 Ma (TR), 2.45 ± 0.23 Ma (TO), 1.44 ± 0.13 Ma (BA), and 0.97 ± 0.41 Ma (PA), correspond to (U-Th)/He ages of 5.30 ± 0.52 Ma (TR), 2.42 ± 0.10 Ma (TO), 1.05 ± 0.05 Ma (BA), and 0.91 ± 0.02 Ma (PA), respectively. The youngest of these U-Pb ages (PA) is corroborated by LA-ICPMS mapping of a grain that yields an age of 1.017 ± 0.067 Ma. The grain mapping reveals no evidence for Pb diffusion and the calculated Pb diffusion temperatures for these megacrysts of ∼1110–1250 °C are significantly greater than Ti-in-zircon apparent temperatures of ∼659 °C. These observations may imply that the U-Pb ages reflect magmatic crystallization and hence, the close similarity of the U-Pb and (U-Th)/He dates observed in all samples documents high zircon megacryst growth rates of ∼1 × 10 −12 (TO) to ∼2 × 10 −14 cm/s (TR).